Islamic Values Contained in the 'Adat Jamuan Kutai' Tradition of the Lemeu Community - Sismi, Ayu; Kartika, Junita; Gustria, Jela (Indonesian Journal of Research in Islamic Studies, 2025)
Background: Traditional customs in Indonesian society play a significant role not only as cultural heritage but also as a medium for religious education. These customs play a crucial role in internalizing Islamic values, enriching religious understanding, and enhancing spiritual practices within social life. Objective: This study aims to describe the traditional Jamuan Kutai procession and examine the Islamic values embedded within the ceremony. The study seeks to highlight the intersection between cultural practices and religious teachings, focusing on how this tradition serves as a means of transmitting Islamic principles to the community. Method: A qualitative approach was used in this field research, applying a case study methodology. Data were collected through direct observation, in-depth interviews, and document analysis. The data analysis employed a descriptive approach, utilizing triangulation of data sources, methods, and time periods to ensure the reliability and validity of the findings. Result:  The study found that the Jamuan Kutai procession, held at night, involves the ceremonial serving of Paunyung Sawo and Punyung Mei as expressions of gratitude. These practices reflect core Islamic values, including faith, worship, and morality. Conclusion:  The Jamuan Kutai tradition proves to be a valuable medium for promoting Islamic education. Through this tradition, Islamic principles are reinforced, blending local customs with religious teachings to enrich the community's cultural and spiritual life. Contribution: This research contributes to understanding how local traditions in Indonesia effectively integrate religious education. It emphasizes the role of cultural practices in reinforcing Islamic values within the community.